Extraction and Characterization of Melanin Nanoparticles from Gallus gallus domesticus Feathers - Iqra Bule,; Anzalna Momin,; Kantilal Nagare,; Dinesh Wanule, (The Bioscan, 2025)
Melanin, a multifunctional biopolymer naturally found in birds, has demonstrated significant potential as a reducing agent. This study reports the extraction and characterization of melanin nanoparticles derived from the waste feathers of domestic chickens (Gallus gallus domesticus). Melanin was extracted using an acid-base method, confirmed through UV-Vis spectroscopy, thin-layer chromatography (TLC), and transmission electron microscopy (TEM). The pigment exhibited a characteristic peak at 230 nm in UV spectroscopic analysis, an TLC exhibit the Rf value of melanin is 0.67, and Transmission electron microscopy reveals the melanin nanoparticle breadth of ~315 nm and had elongated shape with rough-surface area. Its reducing ability was validated through a Methylene Blue Reduction Test (MBRT).